Neurodevelopmental disorder in children believed to have isolated mild ventriculomegaly prenatally. (26th June 2019) - Thorup, E.; Jensen, L. N.; Bak, G. S.; Ekelund, C. K.; Greisen, G.; Jørgensen, D. S.; Hellmuth, S. G.; Wulff, C.; Petersen, O. B.; Pedersen, L. H.; Tabor, A.
ABSTRACT: Objective: To estimate the prevalence of specific neurodevelopmental disorders in children believed to have isolated mild ventriculomegaly (IMV) prenatally in the second trimester of pregnancy, in order to optimize the counseling process. Methods: This was a nationwide registry‐based study including all singleton pregnancies that had first‐ and second‐trimester ultrasound scans in the period 1 st January 2008 to 1 st October 2014, identified in the Danish Fetal Medicine Database and local clinical databases in Denmark. All fetuses diagnosed prenatally with IMV (measurement of the atrium of the lateral ventricles, 10.0–15.0 mm) between 18 and 22 weeks' gestation were followed up in national patient registers until the age of 2–7 years. Information was obtained on the diagnoses of intellectual disability, cerebral palsy, autism spectrum disorder, epilepsy and impaired psychomotor development. Neurodevelopmental disorders were compared between those with postnatally confirmed IMV and a reference population of children in the same age range. Results: Of a cohort of 292 046 fetuses, 133 were found to have apparent IMV on the second‐trimester scan for fetal malformations. In 11 cases, long‐term follow‐up was not possible owing to termination of pregnancy, spontaneous miscarriage, neonatal death or loss to follow‐up. Of the 122 liveborn children followed up until 2–7 years, 15 were identified as having an additional abnormality while 107 were confirmed postnatally to have IMV. Of these 107 children, the diagnosis of a neurodevelopmental disorder was registered in six (5.6%), corresponding to an odds ratio of 2.64 (95% CI, 1.16–6.02), as compared with the reference population. The diagnoses were autism spectrum disorder, epilepsy and impaired psychomotor development. None of these 107 children was diagnosed with intellectual disability or cerebral palsy. Conclusions: Our results show that a confirmed diagnosis of IMV was associated with an increased risk of a neurodevelopmental disorder, as compared with the reference population, but the absolute risk was low and there were no cases of intellectual disability or cerebral palsy. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article has been selected for Journal Club. Click here to view slides and discussion points. This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Trastorno del desarrollo neurológico en fetos con sospecha de ventriculomegalia leve aislada prenatal Objetivo: Estimar la prevalencia de trastornos específicos del desarrollo neurológico en fetos con sospecha de ventriculomegalia leve aislada (IMV, por sus siglas en inglés) prenatal en el segundo trimestre del embarazo, a fin de optimizar el proceso de asesoramiento. Métodos: Este estudio estuvo basado en un registro nacional que incluyó todos los embarazos con feto único a los que se les hizo ecografías en el primer y segundo trimestre entre el 1 de enero de 2008 y el 1 de octubre de 2014, identificados en la Base de Datos Danesa de Medicina Fetal y en las bases de datos clínicas locales en Dinamarca. Todos los fetos diagnosticados prenatalmente con IMV (por medición de la aurícula de los ventrículos laterales, 10, 0–15, 0 mm) entre las semanas de gestación 18 y 22 fueron monitoreados en los registros nacionales de pacientes hasta la edad de 2–7 años. Se obtuvo información sobre los diagnósticos de discapacidad intelectual, parálisis cerebral, trastornos del espectro autista, epilepsia y trastornos del desarrollo psicomotor. Se compararon los trastornos del desarrollo neurológico entre aquellos con IMV confirmada después del nacimiento y una población de referencia de niños en el mismo rango de edad. Resultados: De una cohorte de 292 046 fetos, se encontró que 133 tenían IMV aparente en la ecografía del segundo trimestre realizada para detectar malformaciones fetales. El seguimiento a largo plazo no fue posible en 11 casos debido a la interrupción del embarazo, el aborto espontáneo, la muerte del recién nacido o el abandono del monitoreo. De los 122 niños nacidos vivos a los que se les dio seguimiento hasta los 2–7 años, se identificó a 15 con una anomalía adicional, mientras que a 107 se les confirmó postnatalmente que tenían IMV. De estos 107 niños, se registró el diagnóstico de un trastorno del desarrollo neurológico en seis (5, 6%), lo que corresponde a una razón de momios de 2, 64 (IC 95%: 1, 16–6, 02), en comparación con la población de referencia. Los diagnósticos fueron trastornos del espectro autista, epilepsia y trastornos del desarrollo psicomotor. Ninguno de estos 107 niños fue diagnosticado con discapacidad intelectual o parálisis cerebral. Conclusiones: Nuestros resultados muestran que un diagnóstico confirmado de IMV se asoció con un mayor riesgo de trastorno del desarrollo neurológico, en comparación con la población de referencia, pero que el riesgo absoluto fue bajo y no hubo casos de discapacidad intelectual o parálisis cerebral. 摘要: 相信出生前就患有孤立性轻度脑室扩大症儿童的神经发育障碍 目标: 在妊娠中期，针对相信出生前就患有孤立性轻度脑室扩大症(IMV)的儿童，估算特定神经发育障碍的患病几率，从而优化诊疗流程。 方法: 这是一项全国性注册登记研究，针对所有在2008年1月1日至2014年10月1日期间接受孕早期孕中期超声检测，并列入丹麦胎儿医学数据库和丹麦本地临床数据库的单胎妊娠孕妇。接受产前IMV诊断的所有妊娠期18‐22周胎儿(侧心室心房测量值，10.0–15.0 mm)，2‐7岁之前都要接受全国患者随访登记。获得了智力障碍、脑瘫、自闭症谱系障碍、癫痫和精神运动发育障碍的诊断信息。比较了出生后确诊IMV病患与同一年龄段参考儿童群体之间的神经发育障碍。 一组292 046胎儿研究结果 表明，133个胎儿在孕中期胎儿畸形扫描中有明显的IMV症状，有11例病患因为终止妊娠、自然流产、新生儿死亡或失访而无法进行长期随访。在122个2‐7岁之前接受随访的活产儿童中，15个儿童确定存在其他异常，107个儿童则被确诊为出生后IMV患者。相比参考人群，在这107个儿童中，有6例神经发育障碍诊断记录(5.6%)，对应的几率为2.64 (95% CI, 1.16–6.02)。对应的是自闭症谱系障碍、癫痫和精神运动发育障碍诊断。在这107名儿童中，没有一人诊断出患有智力残疾或脑瘫。 结论: 我们的研究结果表明:相比参考人群，IMV确诊与神经发育障碍风险增加有关，但绝对风险较低，且并无智力障碍或脑瘫病例。